Clinical and imaging outcomes of cerebrospinal fluid-venous fistula embolization. (24th January 2022) - Brinjikji, Waleed; Garza, Ivan; Whealy, Mark; Kissoon, Narayan; Atkinson, John L D; Savastano, Luis; Madhavan, Ajay; Cutsforth-Gregory, Jeremy
Abstract : Background: We report outcomes of spontaneous intracranial hypotension (SIH) patients who underwent transvenous embolization of cerebrospinal fluid-venous fistulas (CSFVFs) confirmed on digital subtraction myelography (DSM) performed at our institution. Methods: This is a retrospective evaluation of a prospectively collected database of SIH patients who underwent transvenous embolization of CSFVFs. Only patients who had fistulas confirmed on DSM performed at our institution were included. All patients had a baseline MRI and an MRI performed at least 90 days post-embolization, as well as clinical evaluation using the six item Headache Impact Test (HIT-6) and the Patient Global Impression of Change (PGIC) scales. Paired t-test was used to report changes in Bern MRI scores and HIT-6 scores at follow-up. Results: 40 patients were included (29 female, 11 male). Mean age was 57.4±10.3 years. Mean Bern score improved from 5.7±3.0 at baseline to 1.3±2.0 at follow-up (p<0.0001). Mean HIT-6 score at baseline was 67.2±11.1 and at follow-up was 41.5±10.1 (p<0.0001). Median PGIC was 1, with 36 patients (90.0%) reporting at least minimal improvement and 32 patients (82.5%) reporting much or very much improvement. Complications included persistent local site pain in 12 patients (30%), suspected rebound intracranial hypertension requiring medical intervention in 7 patients (17.5%), and asymptomatic tiny Onyx emboli to the lungs in 3 patients (7.5%). Conclusions: Transvenous embolization of CSFVFs using Onyx is safe and effective, resulting in significant improvement in headache and overall clinical outcomes in nearly 90% of patients, and substantial improvements in brain MRI abnormalities.